Teachers' perspectives on leadership practices and motivation in Islamic private schools, Southern Thailand - Othman, Azam (EMERALD, 2012)
Purpose – The purpose of this paper is to present teachers’ perspectives on leadership practices and motivation in the context of Islamic private schools in Songkhla, a southern province of Thailand. Design/methodology/approach – A survey method was employed to collect data from teachers in six selected Islamic private schools in Songkhla. Findings – The statistical data indicate that teachers’ motivation is significantly related to principals’ transformational leadership practices, as perceived by teachers. It was found that though teachers perceive their principals exhibited transformational leadership more frequently than transactional leadership, the principals are viewed to display more idealized influence (IIB & IIA) and inspirational motivation (IM) rather than individual consideration (IC) and intellectual stimulation (IS) practices. To strengthen teachers’ motivation in schools, they should exhibit the individual consideration (IC) and intellectual stimulation practices more frequently. Research limitations/implications – This research only focuses on selected Islamic private schools in Songkhla, a southern province of Thailand. Originality/value – The implementation of the Islamic private schools is unique to Muslims in southern Thailand. The views and perspectives of the teachers and administrators are beneficial in moving to the next level of the policy.